INFLUENCIA DE LA "MANCHA AMARILLA" SOBRE LA COMPOSICIÓN QUÍMICA DEL CORCHO Y LA PRESENCIA DE TCA - García Vallejo, M C; Varea, S; Cadahía, E; Fernández de Simón, B (III Congreso Forestal Español, 2001)
The anomaly of cork known as "yellow stain" has been considered as the main responsible for the presence, in some cork stoppers, of 2,4,6-trichloroanisole (TCA), compound that confers the "cork taint" to wine. In this Communication, a comparative study on the chemical composition of cork (suberin, waxes, polyphenols, holocellulose and lignin) and on the presence of chloroanisoles and chlorophenols is carried out with samples of healthy cork and cork affected with that anomaly. The cork with "yellow stain" differed from the healthy cork because of the presence of TCA and the low content of tannins.
Keywords: chemical composition; Cork; yellow stain

Low molecular weight phenols in cork stoppers - Pena-Neira, A; Hernández, T; GARCIA-VALLEJO, M C; Cadahía, E; de Simon, B F; Suarez, J A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1999)
In this work, we study the low molecular-weight polyphenols in cork stoppers obtained from commercial wine bottles and in samples taken at five stages of the cork stopper manufacturing process. The phenolic compounds (acids, aldehydes, and coumarins) were analyzed by high pressure liquid chromatography with photodiode array detector. The results were studied by statistical methods in order to determine the relationship among these compounds and their variability throughout the industrial processing. Discriminant analysis showed that the phenolic composition allows differentiation of each stage in the manufacture of cork stoppers and the different provenances of stoppers obtained from commercial wine bottles. The results showed wide variations in phenolic content among cork stoppers within each region and each winery.
Keywords: Cork; phenolic compounds; stopper manufacturing

Low molecular-weight phenolic compounds in natural and agglomerated cork stoppers - Pena-Neira, A; BartolomÉ, B; Cadahía, E; Hernández, T; Garcia-Vallejo, C; GONZALEZ-ADRADOS, J R; Suarez-Lepe, J A (SCIENCES DES ALIMENTS, 1999)
The low molecular-weight phenolic compounds in cork stoppers used for the closure of wine bottles are studied. Different phenolic acids (gallic, protocatechuic, vanillic, caffeic, ferulic and ellagic), aldehydes (protocatechuic, p-hydroxybenzoic, vanillin, ethylvanillin and coniferilic), and coumarins (aesculetin and scopoletin) were determined in natural cork stoppers (untreated and chlorine-bleached) and in agglomerated cork stoppers (unbleached and peroxide-bleached). The ketone 2,3-dihydroxy-1-guaiacylpropan-1-one and four ellagic-acid-type tannins were detected in natural stoppers. The amount of most of the phenolic compounds studied was higher in the natural cork stoppers than in agglomerated stoppers. In natural cork stoppers, an Increase in the content of caffeic and ferulic acids and vanillin was observed after chlorine bleaching. In agglomerated stoppers however, peroxide bleaching produced a decrease in the content of these same compounds.
Keywords: Cork; low molecular-weight phenolic; Stopper; stopper treatment

Variability of suberin composition of reproduction cork from Quercus suber throughout industrial processing - Conde, E; GARCIA-VALLEJO, M C; Cadahía, E (HOLZFORSCHUNG, 1999)
The chemical composition of suberin was studied in cork planks from three different trees of Spanish Quercus suber at four different stages of the industrial processing of first transformation: stripping (a), first rest (b), boiling followed by open air rest (c1) and boiling followed by store-room rest (c2). The monomeric composition was determined by gas chromatography/mass spectrometry in the product of depolymerization of the free of extractives cork with sodium methoxide-methanol. The average concentrations of the main monomers were: 1-alkanols (C-20-C-26) 4.17 %; alkanoic acids (C-20-C-26) 5.99 %; alpha, omega-alkanedioic acids (C-16-C-24) 6.20 %; omega-hydroxy-alkanoic acids (C-20-C-26) 29.41 %; erythro- and threo-9, 10-dihydroxyoctadecanedioic acids 6.76 %, erythro- and threo-9,10,18-trihydroxyoctadecanoic acids 9.50 %, 9,10-epoxy-18-hydroxyoctadecanoic acid 2.72 % and 9,10-epoxy-octadecanedioic acid 2.93 % and ferulic acid 5.05 %. Significant differences were observed between samples taken at the stripping and after boiling with store room rest, and both groups of samples differed from those picked after the other two processing stages. Ten components were selected as providing the greatest discrimination among stages: 9-octadecenedioic, 18-hydroxy-9-octadecenoic, eicosanedioic and 9,10-epoxy-18-hydroxy-octadecanoic acids, tetracosanol, and five unidentified components.
Keywords: Cork; industrial processin; Quercus suber; suberin

Suberin composition of reproduction cork from Quercus suber - García Vallejo, M C; Conde, E; Cadahía, E; DeSimon, B F (HOLZFORSCHUNG, 1997)
The monomeric composition of suberins from Spanish Quercus suber was determined by gas chromatography/mass spectrometry in the product of depolymerization of free extractives cork with sodium methoxide-methanol. 1-Alkanols (C-20-C-26)(1.8-6.4%), alkanoic acids (C-20-C-24)(2.2-8.1%), alpha,omega-alkanedioic acids (C-16-C-24)(6.1-10.2%) and omega-hydroxy-alkanoic acids (C-20-C-26, being C-22 and C-24 the most abundant)(28.7-37.3%) are identified. The erythro- and threo-9,10-dihydroxyoctadecanedioic (5.4-7.5%), erythro- and threo-9,10,18-trihydroxyoctadecanoic (7.6-11.8%), 9,10-epoxy-18-hydroxyoctadecanoic (1.2-3.1%) and 9,10-epoxy-octadecanodioic acids (1.0-4.4%) and the unsaturated 18-hydroxy-9-octadecenoic (8.1-11.5%) and 9-octadecenedioic (1.5-2.4%) acids are also important components. Ferulic acid (5.3-9.1%) is the main phenolic component of suberin. The studied samples differ in the relative proportion of the different monomers.
Keywords: Cork; epoxy acids; fatty alcohols; fatty and hydrixy-fatty acids; gas chromatography; gas chromatography/mass spectrometry; phenolics; Quercus suber; suberin